Leaf-cutting ant (Atta laevigata Smith) in an African mahogany plantation in Minas Gerais state, Brazil - de Souza, Rodolfo Molinário; Ribeiro, Andressa; Ferraz Filho, Antonio Carlos (EntomoBrasilis, 2021)
Khaya grandifoliola C. DC. (Meliaceae), known as African mahogany, is used in the establishment of commercial plantations for high-value timber production. This work aims to report the first occurrence of the genus Atta in a commercial plantation of this species. An ant nest mound with 105 m2 of loose soil and five active ant holes were observed. Leaves cut into crescent shaped sections and pieces of young branches were found near these holes, in addition to trees with the apical part of their crown partially defoliated. The collected specimens were identified as Atta laevigata Smith (Hymenoptera: Formicidae: Attini), locally known as the glass-head leaf-cutting ant.